2003
DOI: 10.1001/jama.290.17.2277
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Risk Factors in Childhood and Carotid Artery Intima-Media Thickness in Adulthood

Abstract: THEROSCLEROSIS IS THOUGHTto begin in childhood and to develop silently for decades before clinical events such as myocardial infarction or stroke occur. Autopsy studies in children and adolescents have confirmed the presence of preclinical atherosclerotic lesions and shown their associations with antemortem vascular risk factors. [1][2][3] Studies using ultrasound imaging have demonstrated atherosclerotic wall thickening in the arteries of children with risk factors. [4][5][6] Longitudinal studies have shown t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
453
3
13

Year Published

2005
2005
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,511 publications
(481 citation statements)
references
References 34 publications
(36 reference statements)
12
453
3
13
Order By: Relevance
“…Contrary to numerous previous studies we did not find an association between IMT and exercise, smoking, and alcohol drinking 29, 30, 31, 32. Consistent with our result, the association between smoking status and IMT has been reported by Sass and colleagues in middle‐aged but not in young adults 8.…”
Section: Discussionsupporting
confidence: 68%
“…Contrary to numerous previous studies we did not find an association between IMT and exercise, smoking, and alcohol drinking 29, 30, 31, 32. Consistent with our result, the association between smoking status and IMT has been reported by Sass and colleagues in middle‐aged but not in young adults 8.…”
Section: Discussionsupporting
confidence: 68%
“…There were therefore very few hypertensive cases to consider (16/130 men). Six studies considered the association between childhood BMI and carotid intima media thickness (CIMT) (30,(35)(36)(37)(38)(39) , with five of these studies showing a positive association (35)(36)(37)(38)(39) . However, after adjusting for adult BMI only one positive association remained, and this was for the cumulative change in BMI from childhood to adulthood (39) .…”
Section: Independent Effects Of Childhood Obesity On Adult Disease Riskmentioning
confidence: 99%
“…There is evidence that primary high blood pressure (HBP), independent risk factor for the two most common causes of death among adults in Brazil (stroke and heart disease) 1 , has its roots in childhood or adolescence 2 , and several studies have shown that high levels of blood pressure at this age are predictors of hypertension in young adults 3,4 , a phenomenon known as tracking.…”
Section: Introductionmentioning
confidence: 99%